A High‐Throughput Mass‐Spectrometry‐Based Assay for Identifying the Biochemical Functions of Putative Glycosidases. (27th October 2017) - Peng, Tianyuan; Nagy, Gabe; Trinidad, Jonathan C.; Jackson, Joy Marie; Pohl, Nicola L. B.
Abstract: The most commonly employed glycosidase assays rely on bulky ultraviolet or fluorescent tags at the anomeric position in potential carbohydrate substrates, thereby limiting the utility of these assays for broad substrate characterization. Here we report a qualitative mass spectrometry–based glycosidase assay amenable to high‐throughput screening for the identification of the biochemical functions of putative glycosidases. The assay utilizes a library of methyl glycosides and is demonstrated on a high‐throughput robotic liquid handling system for enzyme substrate screening. Identification of glycosidase biochemical function is achieved through the observation of an appropriate decrease in mass between a potential sugar substrate and its corresponding product by electrospray ionization mass spectrometry (ESI‐MS). In addition to screening known glycosidases, the assay was demonstrated to characterize the biochemical function and enzyme substrate competency of the recombinantly expressed product of a putative glycosidase gene from the thermophilic bacterium Thermus thermophilus . Abstract : Losing the right amount of weight : High‐throughput identification of glycosidase biochemical functions, including those from hyperthermophiles, is achieved by observing a correct mass‐loss from individual members of a thermostable library of potential sugar substrates and their corresponding products by using electrospray ionization mass spectrometry (ESI‐MS).